Crustal movement along the Red River Fault zone from GNSS data - Hai, Vy Quoc; Cuong, Tran Quoc; Thuan, Nguyen Viet (Vietnam Journal of Earth Sciences, 2016)
For the first time, recent crustal movement of the Red River Fault was investigated, discussed by segments, based on GNSS data of Thac Ba, Ba Vi - Tam Dao, and Ha Noi networks. From the results of 3 network’s data processing, movements characteristics of fault zones have been synthesized and evaluated as follows: -Absolute crustal movement velocities of study area are approximately 34 mm/year with east-southeast direction. -The Red River Fault has weak activities in rerent times, the relative velocities between the two walls of fault is approximately 1 mm/year. -Next measurement campaigns should be taken in order to determine value and trend of movements more accurately. References Nguyễn Tuấn Anh (chủ biên), 2006: Dự án sản xuất thử nghiệm “Xây dựng hệ thống các điểm Trắc địa sử dụng công nghệ GPS độ chính xác cao trong việc quan trắc biến dạng lớp vỏ Trái đất và cảnh báo thiên tai ở khu vực Việt Nam”. Lưu trữ tại Viện Khoa học đo đạc và bản đồ, Hà Nội. Vy Quốc Hải, 2009: Xác định chuyển dịch tuyệt đối khu vực lưới GPS Tam Đảo - Ba Vì, Tạp chí Địa chất số 311, 3-4, tr.22-30. Vy Quốc Hải, Trần Đình Tô và Ngô Văn Liêm, 2011: Xác định chuyển dịch hiện đại đới đứt gãy Sông Hồng theo số liệu lưới GPS Tam Đảo - Ba Vì (1994-2007). Tạp chí Các Khoa học về Trái Đất, tr.474-479. Ngô Văn Liêm , 2011: Đặc điểm phát triển địa hình trong mối liên quan với địa động lực hiện đại đới đứt gãy Sông Hồng. Luận án Tiến sỹ Địa lý, Hà Nội. Lưu trữ Thư viện Viện Địa chất, Hà Nội. Nguyễn Đăng Túc, 2002: Một số đặc điểm tân kiến tạo hệ đứt gãy Sông Hồng-Sông Chảy. Luận án Tiến sĩ, Hà Nội. Lưu trữ Thư viện Quốc gia, Hà Nội. Rolf Dach, Urs Hugentober and Peter Walser, 2008: Bernese GPS Software Version 5.0. Astronomical Institute, University of Bern.